The Gander Lake and Davidsville Groups of northeastern Newfoundland: a re-examination - Pajari, G. E.; Currie, K. L. (Canadian Journal of Earth Sciences, 1978)
The three-fold division of supracrustal rocks in northeastern Newfoundland into gneiss complex, Gander Lake Group and Davidsville Group is valid and useful. The gneiss complex and Gander Lake Group are separated from the Davidsville Group by a steeply west-dipping reverse fault that was active in Devonian time, but inactive by Carboniferous. Northwest of the fault the ocean floor sequence of ultramafites, mafic volcanic rocks with minor plagiogranites and turbidites of the Davidsville Group proper were disturbed by olistostromes and tectonic slides beginning in late Ordovician time. However, the peak of progressive metamorphism, accompanied by granitoid intrusion and final tectonic emplacement, occurred in the Devonian. Southeast of the fault, the gneiss complex was metamorphosed to sillimanite grade before deposition of the Gander Lake Group. Later metamorphism, affecting both the gneiss complex and Gander Lake Group, was associated with emplacement of megacrystic granite and extended from Devonian into early Carboniferous time. The Gander Lake Group may be time-equivalent to the Davidsville Group. There is no direct evidence either for or against a previously reported late Precambrian to early Phanerozoic orogeny. The observed relations are compatible with obduction of oceanic material in late Ordovician time.